Design and development of aquatic locomotion on robotic shark - Gopalan Srinivasan (2015)
Numerous biomimetic research projects have been piloted to devise robotized underwater propulsion systems with high efficiency that imitates certain aquatic mammals. Inspiring locomotion mechanisms from the aquatic life, this biomimetic project intended to develop a robotic Mako Shark with pectoral, caudal and dorsal fins for gliding and manoeuvring. The chief emphasis of this project was to shape and develop highly efficient aquatic body for the robotic shark keeping in mind the actual shape, motion and behaviour of a Mako Shark. The flapping motion of the undulating shark’s tail was inspired by the short fin Mako Shark; the fastest of all species of sharks in the world. With an array of pictures and videos of Mako, the pulling mechanism involved in the propulsion was incorporated in the project. One of the major findings during the course of research was the effects of dorsal and pectoral fins. In reality, the bones and muscle tissues of a shark are denser than the water around it. In order to maintain the depth and float underwater, the shark tries to increase the buoyancy. The phenomenon involved is called dynamic lifting. The shark uses pectoral fins to create that lift, which is similar to that of the wings of an aeroplane or a bird. As the shark propels forward, the pectoral fins of the shark provide the required lift to maintain a certain depth. Stability of the shark is provided by the dorsal fin. Dorsal Fin serves to prevent the fish from toppling or rolling and helps in manoeuvring sharply. These desired motions were programmed to mimic a lifelike motion for the robotic shark. A full working prototype was built and assembled. Its propulsive motion was tested and investigated. The test results and corresponding conclusions are presented in this report. It was inferred that the movement of the dorsal fin provided the essential force to counter the gravitational force and prevented the shark from tilting towards the sides.However, more studies and testing have to be executed to boost the hydrodynamics of the robot.